Caracterização física e biológica do solo após aplicação de herbicidas em plantios de acácia-negra (Acacia mearnsii De Wild.) no Rio Grande do Sul - Perrando, Edison Rogério (2008)
The study of soil quality biological indicators in areas classified as forest production units is important to understand the ecological processes that occur in these systems. Monitoring the soil fauna in modified environments, when management practices involve chemical products in the environment, is an instrument that allows to evaluate not only the soil quality but also the proper functioning in a production system, since the soil fauna acts in decomposition and nutrient cycling, as well as in soil physical, chemical and biological properties. The objective of this study was to evaluate the herbicide application in a black wattle area (Acacia mearnsii De Wild.). Thus, the study was divided in three chapters. The first chapter aimed to evaluate the meso and macrophauna under different kinds and intensities of herbicides on the ground using the principal component analysis (PCA). The study was developed at Fundação Estadual de Pesquisa Agropecuária (Fepagro-Unidade Florestas) in Santa Maria/RS. The treatments were allocated as Randomized Blocks Design, with four repetitions per treatment, totalizing 64 experimental units, where two sampling plots were installed per unit using the meso and macrophauna capture PROVID method. The used herbicides were Glyphosate (4.0 l ha-1), Imazapyr (3.0 l ha-1), Oxyfluorfen (4.0 l ha-1) and Pendimethalin (3.0 l ha-1) besides hand cleaning and control without herbicide. The collects were done in the four seasons of the year (winter, spring, summer and autumn). From the calculated faunistic indexes, the taxonomic group average richness varied from 5.2 in the winter to 9.3 in the summer. The Shannon (H) diversity index was similar among all kinds and intensities of applied herbicides. This index (H) was different only between the seasons, varying from 0.58 in the spring to 1.21 in the summer. The PCA between the response and predictor variables clearly separated the component formation (taxonomic groups), significantly influenced by the kind of herbicides and application intensity. However, in PCA with additional predictor variable for the four most representative taxonomic groups (Araneae, Orthoptera, Collembola e Hymenoptera), it was observed that organism density in the group constituted by Collembola is strongly associated with the precipitation in the spring, whereas ants, Orthoptera, and spiders have their density better explained by the variable temperature. Different herbicides, as well as the intensity of the application on the ground caused no negative effects upon the biological parameters evaluated in the study, being the diversity and the density of meso and macrophauna conditioned only to the seasonal variations along the year. The study approached in the second chapter aimed to evaluate the influence of different kinds and intensities of herbicide application upon the soil physical properties, like density, macro, micro and total porosity, and aggregates average diameter (AAG). The experimental plot was the same described in chapter one. Two collections were done (before planting and after all herbicides application). Two soil samplings were collected in planting and interplanting seedling rows. The obtained results in the second collection showed that there is no significant difference between the evaluated parameters. For soil density, the highest values were found in treatments without herbicide (1.38 Mg m-3 in hand cleaning and 1.32 Mg m-3 in control). For macro, micro and total porosity the values were similar among them, for all kinds of tested herbicides, as well as for AAG. There was no herbicide direct influence upon the soil physical properties, since the weed competition was partially controlled, mainly in inter row seedlings planting, that might have contributed to maintain the soil physical structure in this area. In planting row, there was a fast soil particle reaccommodation because of the seedling roots. The third chapter aimed to evaluate the influence of herbicide application upon the symbiotic association between Rhizobium and the root systems from black-wattle seedlings, cultivated in plastic vessels under controlled environmental conditions in greenhouse. The study was established in Randomized Blocks Design, with four repetitions and ten plants per treatment, which were constituted by the same herbicides and doses mentioned in chapter one, besides a treatment without herbicide (control). The results in this study showed significant differences between the treatments and the variable dried biomass from rhizobic nodules in the black-wattle seedlings root system. All the herbicides used in vessels substrates induced the nodules formation, highlighting the herbicide Oxifluorfen (0.532 g plant-1), that showed a nodules biomass gain of 128.3% related to the control (0.233 g plant-1). Except for Glyphosate, the correlations between nodules biomass and the variables height, above ground biomass, and root biomass were all positive and significant. This way, the use of herbicide in the evaluated microenvironment caused no negative influence upon the physical and biological components (field), as well as on the microbiological component evaluated (greenhouse).